THE PUBLIC SECTOR IN ADOPTION FROM M-GOVERNMENT - Pastor Carrasco, Carlos Alberto (2014)
The rapid development of wireless technology and mobile devices is changing fundamental aspects of modern society. These advances provide a new con-quest in increasing the quality of life of citizens in so far that will improve their mobility, which is altering your lifestyle, the way they relate and communicate with others, and the way work. This phenomenon has been led by the unstoppable expansion of cell phone use: no known technology (even the INTERNET) has been imposed so quickly, and has evolved so much in so little time. Mobile Government (m-Government) is one of the major new developments within the electronic government (e-Government). The promise of m-Go-vernment to provide greater access to government information being made in many countries, both developed and developing. In this paper a comparative analysis of mobile applications in the countries is pre-sented to provide an analysis of trends in developing a framework and discuss the implications for policy makers, government officials and solution providers of Information Technology .